The Role of Counselors in Reducing Mobile Phone Usage Habits Among Students at SMAN 1 Tulungagung - Adibah, Almas Dwi; Widi, Citra Ayu Rahmaning; Dewi, Innaya Rahmania; Zamroni, Zamroni; Mardiana, Farida (Universitas Negeri Malang, 2024)
The study aims to understand the role of counselors in reducing the habit of mobile phone usage among 10th-grade students at SMA Negeri 1 Tulungagung. This research employs a descriptive qualitative approach using a case study method. Data collection techniques include interviews and observations. The subjects of this study are counselors and several 10th-grade students at SMA Negeri 1 Tulungagung. The results indicate that mobile phone usage habits among students impact their self-awareness, decrease their motivation to learn, and reduce their empathy. In addressing this issue, counselors play a role by providing informational services, classical guidance services on appropriate mobile phone usage, and counseling services. Additionally, home visits and parent or guardian meetings are conducted as follow-up measures for students. Counselors at SMA Negeri 1 Tulungagung also perform referrals for cases of students who are severely addicted to their mobile phones. Keywords: Counselors; Role, Reducing, Mobile Phone Usage, students